?AUTECOLOGICAL STUDIES OF EXOTIC PLANT HIBISCUS SABDARIFFA L. (ROSELLE), A MU TIPURPOSE PLANT, FOR ITS INTRODUCTION AND CULTURE - ASKARI, ABID; SOIANGI, M. SALIH; AHMED, S. IFTIKHAR (Biological Sciences - PJSIR, 1995)
Hibiscus sabdariffa L. (Roselle) is a plant of economic importance.The data on all aspects of its autecology and culturehavebeenreportedandamethodofitscultivationhasbeendevelopedwhichgavegood(peracre)yield.Theseeds were found tobe viable upto 85%.The optimum temperature rangeand photoexposurefor germination werefound to be 25-35°C and 12hrs respectively. The crop needed irrigation twice in Karachi area climatic condition for the best growth.The viabilityofseeds collectedfromtheharvestedcrop showedgradual decreasecineyear after collection and further on.